Brønsted acid catalyzed α-alkylation of aldehydes with diaryl methyl alcohols - Xing, Chong (2012)
A proton does the two jobs: Brønsted acids alone catalyze the α-alkylation of aldehydes with diaryl alcohols. In this type of transformation, the acid-catalysis approach offers a broader substrate scope compared to the previously used enamine catalysis methods. The acid plays two important roles: one is to mediate the alcohol dehydration for carbocation formation; the other is to accelerate the rate-determining aldehyde enolization.